Psychogenic purpura (Gardner-Diamond syndrome). - Recurrent spontaneous painful ecchymosis and systemic symptoms. - Amichai, B.; Gabay, B.; Grunwald, M.; Shemer, A.; Nemet, D. (European Journal of Pediatric Dermatology, 2013)
Gardner-Diamond syndrome is a rare clinical syndrome of recurrent bruising or bleeding, usually following a physical or psychosocial stress. Although most commonly affecting women, it has been described in children and adolescents. Here is reported a case in a 16-year-old adolescent.